Trypsin polymorphism and modulation in Penaeus vannamei (Boone, 1931): a review - Aguiñaga-Cruz,Jazmine Asusena (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2019)
ABSTRACT The trypsin enzyme of white shrimp Penaeus vannamei is a polymorphic molecule, which longest isolated and sequenced cDNA encoded a pre-proenzyme of 255 amino acids. Three of the described sequences are translated in the digestive gland, and SDS-PAGE detects the isoforms. The three isoforms named C, B and A are distributed by an individual to originate three trypsin phenotypes (CBA, CB and CA) that have already been isolated and characterized by defining theirs biochemical and kinetical differences. The CBA phenotypes exerted higher hydrolytic capabilities than the others. The trypsin phenotypes are inherited in a Mendelian fashion, and external or internal factors do not modulate them. In commercial hatcheries in Sinaloa, México, the most abundant phenotype was CBA, followed by CB and CA. The following two hypotheses may explain this finding: phenotype CA is not chosen throughout the selection process of breeders because they do not fit the anatomical characteristics desired by professionals in aquaculture or it is possible that shrimps with the CA phenotype die during the early stages of development. Two experimental designs were developed trying to explain such hypotheses and, in both experiments, CA phenotype frequency declined to zero when shrimps reached around 5 g of body weight. So far, no evidence explains the mortality of juvenile shrimps with phenotype CA. Research is needed to explain why CA phenotypes disappeared, how the survival of this phenotype can be improved, and how to produce shrimps with the most hydrolytic capability in support of the shrimp aquaculture industry.